Internal auditing - Bigg, Walter W.; Davies, John Ogwen (London : H. F. L. Publishers Ltd, 1959)
The authors sees the need for a work on modern internal auditing. In the past, reliance has been placed on the literature published in the United States of America. It is thought that the growth of internal auditing in this country during recent years warrants a book written with British concepts in mind.
Previous ed. (B53-13653) 1953
Includes index.
ahz 02/04/2019
Loans
Keywords: Internal auditing